Hepatocellular carcinoma is accelerated by NASH involving M2 macrophage polarization mediated by hif-1αinduced IL-10. (2nd October 2016) - Ambade, Aditya; Satishchandran, Abhishek; Saha, Banishree; Gyongyosi, Benedek; Lowe, Patrick; Kodys, Karen; Catalano, Donna; Szabo, Gyongyi
ABSTRACT: Obesity-related inflammation promotes cancer development. Tissue resident macrophages affect tumor progression and the tumor micro-environment favors polarization into alternatively activated macrophages (M2) that facilitate tumor invasiveness. Here, we dissected the role of western diet-induced NASH in inducing macrophage polarization in a carcinogen initiated model of hepatocellular carcinoma (HCC). Adult C57BL/6 male mice received diethyl nitrosamine (DEN) followed by 24 weeks of high fat–high cholesterol–high sugar diet (HF-HC-HSD). We assessed liver MRI and histology, serum ALT, AFP, liver triglycerides, and cytokines. Macrophage polarization was determined by IL-12/TNFα (M1) and CD163/CD206 (M2) expression using flow cytometry. Role of hif-1α-induced IL-10 was dissected in hepatocyte specific hif-1αKO and hif-1αdPA (over-expression) mice. The western diet-induced features of NASH and accelerated HCC development after carcinogen exposure. Liver fibrosis and serum AFP were significantly increased in DEN + HF–HC–HSD mice compared to controls. Western diet resulted in macrophage (F4/80 + CD11b + ) infiltration to liver and DEN + HF–HC–HSD mice showed preferential increase in M2 macrophages. Isolated hepatocytes from western diet fed mice showed significant upregulation of the hypoxia-inducible transcription factor, hif-1α, and livers from hif-1α over-expressing mice had increased proportion of M2 macrophages. Primary hepatocytes from wild-type mice treated with DEN and palmitic acid in vitro showed activation of hif-1α and induction of IL-10, a M2 polarizing cytokine. IL-10 neutralization in hepatocyte-derived culture supernatant prevented M2 macrophage polarization and silencing hif-1α in macrophages blocked their M2 polarization. Therefore, our data demonstrate that NASH accelerates HCC progression via upregulation of hif-1α mediated IL-10 polarizing M2 macrophages.